Translation and interpretation of Abay’s politikal – social Lurics into Turkic languages - L. N., Daurenbekova; S. K., Imanberdiyeva; B. D., Dautova; G. S., Rainbekova; G. M., Toktymanova (Opción, 2020)
In today’s fast-growing field of education and science, it is important to strengthen the historical ties and unity of the Turkic people, to study the outstanding Turkic people in more detail and to introduce them to the world. One of these outstanding people is Abay Kunanbayuly. Abay raised not only the problems of the Kazakh people, but the common humanity as a whole. The article evaluates Abay’s translations into Turkish and considers ways to interpret them in Turkish. The purpose of the resaecrh is to determine the degree of transformation of the Abau‟s heritage in the Turkic countries.